Evaluation of the Association Between Sleeping Arrangements and Breastfeeding in Infants: A Cross-Sectional, Single Unit Study - Tuğba Burcu Öztürk; Şule Gökçe; Merve Tosyalı; Feyza Umay Koç (Galenos Yayinevi, 2023)
Aim:The bed-sharing option has been reported to positively encourage breastfeeding frequency in the literature. However, an association between sudden infant death syndrome (SIDS) and infant bed-sharing has also been identified. The present study aimed to determine the effects of mother-infant bed-sharing and room-sharing on breastfeeding and sleep patterns and whether there is any increased risk of SIDS.Materials and Methods:We conducted a cross-sectional study among 507 mother-infant dyads between August, 2017 and August, 2018. Bed-sharing was defined as sharing a bed or mattress; room-sharing was defined as sharing the same room for any part of the night. The validated Sleep Questionnaire form was used to assess infant sleep characteristics. Potential predictors of bed-sharing were evaluated via logistic regression models (age, education, etc.).Results:In the study period, 507 mother-infant dyads were included. The rate of room-sharing was 78.1%, and the rate of bed-sharing was 12.4%. Additionally, the rate of sleeping in a different room was 9.5%. All infants aged 1-5 months who shared a bed with their mother were breastfed, while 94% of those who did not share a bed were breastfed. For 6-12-month-old babies, the breastfeeding frequency was 86% for those who shared a bed, whereas 77% of those who did not share a bed were breastfed. However, the bed-sharing modality was not statistically shown to increase the frequency of breastfeeding [odds ratio (95% confidence interval); 0.362 (0.130-1.01)] (p=0.052).Conclusion:Sharing a bed remains popular for infants' sleep arrangements. In our study, the majority of infants slept in separate cribs. This study revealed that mother-infant bed sharing increased breastfeeding frequency. Moreover, mother-infant bed sharing delayed the age at which babies with sleep disorders stopped breastfeeding.